Expression and Regulation of the sodF Gene Encoding Iron- and Zinc-Containing Superoxide Dismutase in Streptomyces coelicolor Müller - Kim, Eun-Ja (American Society for Microbiology, 1998)
Streptomyces coelicolor Müller contains two superoxide dismutases (SODs), nickel-containing (NiSOD) and iron- and zinc-containing SOD (FeZnSOD). The sodF gene encoding FeZnSOD was isolated by using PCR primers corresponding to the N-terminal peptide sequence of the purified FeZnSOD and a C-terminal region conserved among known FeSODs and MnSODs. The deduced amino acid sequence exhibited highest similarity to Mn- and FeSODs from Propionibacterium shermanii and Mycobacterium spp. The transcription start site of the sodF gene was determined by primer extension. When the sodF gene was cloned in pIJ702 and introduced into Streptomyces lividans TK24, it produced at least 30 times more FeZnSOD than the control cells. We disrupted the sodF gene in S. lividans TK24 and found that the disruptant did not produce any FeZnSOD enzyme activity but produced more NiSOD. The expression of the cloned sodF gene in TK24 cells was repressed significantly by Ni, consistent with the regulation pattern in nonoverproducing cells. This finding suggests that the cloned sodF gene contains the cis-acting elements necessary for Ni regulation. When the sodF mRNA in S. coelicolor Müller cells was analyzed by S1 mapping of both 5′ and 3′ ends, we found that Ni caused a reduction in the level of monocistronic sodF transcripts. Ni did not affect the stability of sodF mRNA, indicating that it regulates transcription. S. lividans TK24 cells overproducing FeZnSOD became more resistant to oxidants such as menadione and lawsone than the control cells, suggesting the protective role of FeZnSOD. However, the sodF disruptant survived as well as the wild-type strain in the presence of these oxidants, suggesting the complementing role of NiSOD increased in the disruptant.